Amyloid Imaging With 11C-PIB in Patients With Cognitive Impairment in a Clinical Setting: A Visual and Semiquantitative Analysis. (January 2016) - Jiménez-Bonilla, Julio F.; Banzo, Ignacio; De Arcocha-Torres, María; Quirce, Remedios; Martínez-Rodríguez, Isabel; Sánchez-Juan, Pascual; Carril, José M.
Abstract : Purpose: The aim of this study was to evaluate amyloid imaging with 11 C-PIB PET/CT in the study of cognitive impairment in a clinical setting. Patients and Methods: The study included 64 patients, with a mean age of 65 years, classified as subjective memory complaints (SMCs; n = 8), nonamnestic mild cognitive impairment (NA-MCI; n = 10), amnestic MCI (A-MCI; n = 19), prodromal Alzheimer disease (AD; n = 12), suspicion of frontotemporal dementia (n = 8), Lewy bodies dementia (DLB; n = 2), and cortical degeneration (CD; n = 5). Ten healthy controls (HCs), with a mean age of 59 years, were also included. 11 C-PIB was acquired 60 minutes after IV injection of 555 MBq 11 C-PIB. A visual and semiquantitative analysis was performed. Results: In HC, 11 C-PIB was negative in 9 and positive in 1. Of the 64 patients, 11 C-PIB was negative in 27 (42%) and positive in 37 (58%). 11 C-PIB was positive in 3 of 8 SMC, in none of 10 NA-MCI, in 14 of 19 A-MCI, in 10 of 12 prodromal AD, in 3 of 8 frontotemporal dementia, and in the 2 and 5 DLB and CD patients. The semiquantitative results in terms of mean global SUV ratio were 1.13 for HC, 1.36 for SMC, 1.07 for NA-MCI, 2.01 for A-MCI, 2.37 for prodromal AD, 2.75 for DLB, and 2.44 for CD. Conclusions: In a clinical setting, 11 C-PIB scan had a relevant contribution on patients with cognitive impairment, excluding AD in a high proportion of MCI patients and differentiating AD from other dementias. In A-MCI, 11 C-PIB revealed β-amyloid deposit in 74%, whereas it was negative in all NA-MCI patients.